Küresel Enerji Jeopolitiğinde Türkiye: Fırsatlar ve Riskler / The Position of Turkey in Global Energy Geopolitics: Opportunities and Risks - Oral, Muhammed; Özdemir, Ünal (Journal of History Culture and Art Research, 2017)
Abstract Turkey has various social, economic, cultural and geostrategic advantages and opportunities thanks to its location. However, it is also located between the Middle East, Balkans, and Caucasus, which are among the most depraved and unstable places in the world. This brings geopolitical risks to Turkey. With respect to energy geography, Turkey draws attention both as a center and as a natural route country that connects supply and demand territories. More than 70% of the world’s oil and natural gas reserves and about 30% of global consumption currently take place in Europe. Accordingly, Turkey is a terminal country with its energy demand security for resource territories and with its energy supply security for supply territories. The purpose of this study is to discuss the roles of Turkey with its strategic location in the energy geopolitics centered on oil and natural gas. The study uses the data provided by organizations that engage in significant international and national activities in the industry such as the International Energy Agency (IEA), U.S. Energy Information Administration (EIA), British Petroleum (BP), World Energy Council (WEC), and the Republic of Turkey Ministry of Energy and Natural Resources. Thus, this study uses a quantitative research method through the collection and analysis of secondary data. Öz Türkiye konum itibariyle sosyal, ekonomik, kültürel ve jeostratejik açıdan çeşitli avantajlara/fırsatlara sahiptir. Ancak söz konusu coğrafya, aynı zamanda dünyanın en buhranlı, istikrarsız mekânlarından olan Orta Doğu, Balkanlar ve Kafkaslar bölgesinde yer almaktadır. Bu durum Türkiye için jeopolitik riskleri de beraberinde getirmektedir. Enerji Coğrafyası özelinde ise Türkiye, bir merkez ve arz-talep coğrafyalarını birleştiren doğal bir güzergâh ülkesi olarak dikkat çekmektedir. Mevcut durum itibariyle dünya petrol ve doğal gaz rezervlerinin %70’ten fazlası ve küresel tüketimin yaklaşık %30’u Avrupa tüketim coğrafyasında gerçekleşmektedir. Buna göre Türkiye, kaynak coğrafyaları için enerji talep güvenliği, arz coğrafyaları için de enerji arz güvenliği yönüyle terminal bir ülkedir. Bu çalışmanın amacı, stratejik bir noktada konumlanan Türkiye’nin petrol ve doğal gaz eksenli oluşan enerji jeopolitiğinde ne gibi rollere sahip olduğunu tartışmaktır. Araştırmada; IEA, EIA, BP, WEC, ETKB gibi sektörde uluslararası ve ulusal ölçekte önemli çalışmalar yürüten kuruluşların verilerinden yararlanılmıştır. Dolayısıyla araştırmada ikincil verilerin elde edilmesi ve değerlendirilmesi çerçevesinde nicel metot uygulanmıştır.